Investigating the Impact of Bank-specific Determinants on Stock Price of Listed Commercial Banks: Evidence from Emerging Economy - Rubaiyath, Akila; Lalon, Raad Mozib (International Journal of Economics and Financial Issues, 2022)
This paper attempts to investigate the impact of bank-specific determinants on the stock price of Dhaka Stock Exchange (DSE) listed commercial banks in Bangladesh. Several bank-specific factors such as Book to Market Ratio, Return on Equity, Price/Earnings to Growth Ratio, Cash Flow per Share, Debt to Equity Ratio, Earnings per Share, Dividend per Share, Bank Size and Institutional Ownership Percentage have been analyzed for this study and tried to see the impact of each variable on the change in market price of share of 10 listed commercial banks spanning from 2011 to 2020. In empirical discussion four estimation models such as Fixed effects, Random effects, GLS, and Pooled OLS approach have been used to ensure the robustness of the models. To examine the validity of the models chosen for this study, the model specification test and many diagnostic checks were used, including the test of heteroskedasticity, the cross-sectional dependence test, the test of autocorrelation and the unit root test, etc. Our investiagtion reveals that only Bank Size and Book to Market Value explanatory variables are found significantly responsible for fluctuation in the change in share price of banks, contributing to the current literature by revealing the importance of bank-specific factors that include all metrics in their calculation. As a result, Bangladesh's DSE-listed banks should take appropriate measures to boost their stock values, such as attempting to improve the ratio that has a positive impact on the share price while decreasing the ratio that has a negative impact.